Nikolai Demidov : becoming an actor-creator - Demidov, N. V. (NikolaÄ VasilÊ¹evich), 1884-1953 (Routledge, 2016)
At the time of his death, Stanislavsky considered Nikolai Demidov to be 'his only student, who understands the System'. Demidov's incredibly forward-thinking processes not only continued his teacher's pioneering work, but also solved the problems of an actor's creativity that Stanislavsky never conquered. Despite being one of the original teachers of the Stanislavski system, Demidov's name was little known either in his native Russia or the wider world until the turn of the 21st Century. Since then, his extensive works have been published in Russian but are yet to find their way to the English-speaking world. His sophisticated psychological techniques, stimulation of creativity, and methods of developing the actors themselves are now gaining increasing recognition. This book brings together Demidov's five volumes on actor training. Supplementary materials, including transcriptions of Demidov's classes, and notes and correspondence from the author make this the definitive collection on one of Russian theatre's most important figures.